Representações do exílio e da melancolia: uma leitura das crônicas de Berna, de Clarice Lispector - Souza, Tayza Codina de [UNESP] (2015)
This work undertakes an interpretative reading of The Chronicle of Bern written by Clarice Lispector and published in Jornal do Brasil between 1967 and 1973 highlighting the themes of exile and melancholy. It aims to demonstrate how the literary production of the writer is linked to her own experiences of displacement and segregation represented in the texts by the use of fictionalization of enunciators that transit in a subjective state of melancholy and emptiness and do not identify with the foreign space and the others who live there. The theoretical basis of the concept of recreating the experience focuses on Garramuño (2012), the exile literature can be found in Nancy (1996) and Rouanet (2008) whereas the support for the discussion of melancholy aesthetics came mainly from Freud (2011), Hassoun (2002) and Lambotte (2000).The writer explores the perception of urban public space in the chronicle offering a feeling that captures the everyday and represents it in a mixture of trip chronicle and lyric reflection. The objctive is to present the aspects of Clarice Lispector's literary project mobilized in the creation of The Chronicle of Bern which can be individually read, but can also be read all together as if they were a single text. Then, it develops a process of searching for evidence for the recreation of the literary texture of the work through the chronicle analysis and the recurrence of these in the novel A Cidade Sitiada, paying attention to the concern of the writer to return to text that has been already published to give another meaning and rebuild it developing a written in Palimpsest